PENGETAHUAN GIZI DAN PENGGUNAAN UANG JAJAN DALAM MEMENUHI ASUPAN ENERGI PADA ANAK SEKOLAH DASAR - Hendrayati Hendrayati; abdullah tamrin; Ramlan Asbar; Hikmawaty Mas'ud; Suciyati Suciyati (Jurusan Gizi Poltekkes Kemenkes Makassar, 2017)
Background: School-aged children are an investment nation. Children are the next generation of the nation. Quality of the nation in the future determined the quality of children today. Efforts to improve the quality of human resources must be done early and systematic. Growing development of school-age children is optimal depending on the provision of nutrients with good quality and quantity.Method: This research is descriptive, to get description of nutrition knowledge, the use of pocket money and nutritional status of elementary school children Inpres Tangkala 2 Sudiang Raya Biringkanaya Makassar. The population of this study were all students of Class V numbered 87 students who were present at the time of the research took place the questionnaire which was distributed at the beginning of the data collection. Primary data The data taken include the identity of respondents knowledge of nutrition, the use of pocket money and nutritional status of school children.Result : The results showed that 80 samples on good nutrition knowledge as much as 31.3% and less as much as 68.8%, indicating that sample of the use of pocket money more than 50.0% quite 46.3%, less as much as 3.8%., And showed that the sample of good energy intake was 16,3%, less 82,55%, and more 1,3%.Conclusion: A total of 68.8% of students who have knowledge of nutrition is quite good, 46.3% of students who have enough pocket money and good energy intake 16.3% of students.Recommendation : Elementary school children was have nutrition knowledge good for use pocket money and intake energy status.Keyword : Nutrition knowledge, Pocket money, Intake energy